A Horthy-korszak jóléti állama, eredményei a gazdasági modernizáció tükrében = The welfare state of the Horthy era, its achievements in light of the economic modernization - Szávai, Ferenc (Közép-Európai Közlemények, 2017)
Can the exact social policy of the Horthy era be written? What could limit our options? On the one hand could the diff erences in approach, the scarcity of available resources, and their real social impact make our task more diffi cult? The Hungarian social policy of the era followed its own course. It had no defi cits; it had no curves, but has led to a diff erent kind of modernity. Approaching it from the aspect of economic history after the First World War it had neither the time, nor the opportunity to undergo a development akin to its Western counterparts. At least there was some continuity with existing legal regulation. In 1930 social policy expenditures were 5,2% of the GDP, which was considered high in international comparison. Naturally the dynamics of the growth of pension insurance is true of the Hungarian system as well as the poor coverage in the case of agricultural workers. Every change is to be found in the junction of economic growth, decisions and international trends.